Evolution of Pharmacotherapy for Hypercholesterolemia: Efficacy and Adverse Effect Profile from Bile acid sequestrants to Modern Molecular Therapies - Kozłowski, Sebastian; Zdunek, Marta; Stodulski, Maciej; Bulicz, Anna; Kasprzycka, Izabela; Kukla, Monika; Kowalczyk, Olga; Dziarnowska, Joanna; Fiks, Justyna; Kmiecik, Izabela (Quality in Sport, 2026)
Dyslipidemia, particularly elevated levels of low-density lipoproteins (LDL), plays a key role in the pathogenesis of atherosclerosis and its cardiovascular complications. The aim of this paper is to present the evolution of therapeutic strategies aimed at reducing LDL- C levels, with particular emphasis on modern molecular therapies [1]. Mechanisms regulating lipid metabolism are discussed, including the role of the LDL-LDLR-PCSK9 axis [2]. Classical treatment methods, such as bile acid sequestrants, statins, and ezetimibe, as well as newer therapeutic options, including bempedoic acid, PCSK9 inhibitors, and siRNA-based therapies, are presented. Future directions in pharmacotherapy, such as CETP inhibitors, evinacumab, and gene therapies using CRISPR-Cas9 technology, are also addressed. Modern treatment strategies enable significant reduction of LDL-C levels and a more precise therapeutic approach. Their use aligns with the development of personalized medicine, although further evaluation of long-term safety is required [3,4].